Canada : Financial Sector Assessment Program-Stress Testing-Technical Note. (IMF Staff Country Reports; Country Report, 2014)
This paper examines the stress testing module of the 2013 Financial Sector Assessment Program (FSAP) update for Canada. The IMF report highlights the three major segments of the domestic financial covered during the stress tests. The bank solvency stress tests suggest that while all banks would fall below the Canadian 'all-in' Common Equity Tier 1 (CET1) supervisory threshold during severe economic distress, the resulting recapitalization needs are manageable. This IMF report provides recommendations for the Canadian authorities, derived from this joint exercise, to enhance the individual components of their stress testing framework.